Fabrication and Characterization of Gel Beads of Whey Isolate Protein–Pectin Complex for Loading Quercetin and Their Digestion Release - Xu Wang; Huaping Xie; Chenshan Shi; Piotr Dziugan; Hongfei Zhao; Bolin Zhang (Gels, 2021)
In this study, emulsion gel beads for loading quercetin were prepared through an emulsification/gelation process using whey protein isolate (WPI) and pectin. Emulsion gel beads’ properties were investigated by different pectin content. Additionally, the physicochemical properties, morphology and quercetin release properties from beads were explored. Firstly, electrical characteristics and the rheology of bead-forming solutions were measured, revealing that all systems had strong negative charge and exhibited shear-thinning behavior. The textural results demonstrated that the properties of emulsion gel beads were improved with increasing the content of pectin. It was also confirmed that crosslinking was formed between WPI emulsion and pectin by Fourier Transform Infrared (FTIR) analysis and thermogravimetric analysis (TGA). In addition, the shape of the beads was spherical or ellipses with smooth surfaces and they had a tight gel network of internal structures, which was visualized by using electron microscopy (SEM). Finally, the amount of quercetin released in vitro was gradually decreased with increasing pectin content; it was as low as 0.59%. These results revealed that WPI emulsion–pectin gel beads might be an effective delivery system for quercetin as a colon target and are worth exploring further.